2022
DOI: 10.3389/fcvm.2022.922696
|View full text |Cite
|
Sign up to set email alerts
|

Conduction disorders after transcatheter aortic valve implantation: A comparison between SAPIEN 3 and SAPIEN 3 Ultra balloon-expandable valves

Abstract: BackgroundConduction disorders (CD) are the most common complications after Transcatheter Aortic Valve Implantation (TAVI). The last generation of Edwards balloon expandable valves, the SAPIEN 3 Ultra (S3U), is provided with an external sealing skirt that aims to further reduce paravalvular leakage (PVL) compared to SAPIEN 3 (S3) and could potentially lead to higher CD rate. We sought to investigate the rate of new-onset CD in patients undergoing TAVI with the S3 or S3U valve.MethodsWe included 582 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The 30-day mortality of 3.7% associated with Portico valve prostheses is comparable to earlier reported mortality rates in other trials ( 11 14 ). In contrast, the ES3 group showed a relatively low 30-day mortality rate of 0.9%, which aligns with previously reported data ( 15 , 16 ). Considering the preprocedural calculated EuroScore II for each group, the expected mortality rates were anticipated to be quite similar.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 30-day mortality of 3.7% associated with Portico valve prostheses is comparable to earlier reported mortality rates in other trials ( 11 14 ). In contrast, the ES3 group showed a relatively low 30-day mortality rate of 0.9%, which aligns with previously reported data ( 15 , 16 ). Considering the preprocedural calculated EuroScore II for each group, the expected mortality rates were anticipated to be quite similar.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Murray et al reported a rate of 25.5% ( 18 ), followed by De-Torres et al reporting a rate of 19.1% in 2016 ( 19 ). Most recently, Monizzi et al described a substantially lower rate of 6.3% in 2022 ( 16 ). The rate of 13.1% of PPM implantation in ES3 in our study aligns with the decreasing trend reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%